2008
DOI: 10.1021/jm8006195
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Compounds Based on a Natural Product Consensus Pharmacophore

Abstract: We report the design and highly enantioselective synthesis of a potent analog of the spliceosome inhibitor FR901464, based on a non-natural product scaffold. The design of this compound was facilitated by a pharmacophore hypothesis that assumed key interaction types that are common to FR901464 and an otherwise unrelated natural product (pladienolide). The synthesis allows for the preparation of numerous novel analogs. We present results on the in vitro activity for this compound against several tumor cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(123 citation statements)
references
References 24 publications
3
117
0
3
Order By: Relevance
“…We also found that SSA (1), PB (2), and HB (3) very likely interact with the same site on SF3B1, which strongly supports the presence of a common pharmacophore between the compounds, as predicted by Webb and co-workers (Lagisetti et al 2008, although the full features of the pharmacophore are still not fully apparent. PB (2) and HB (3) resemble each other with a side chain linked to a ring structure.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We also found that SSA (1), PB (2), and HB (3) very likely interact with the same site on SF3B1, which strongly supports the presence of a common pharmacophore between the compounds, as predicted by Webb and co-workers (Lagisetti et al 2008, although the full features of the pharmacophore are still not fully apparent. PB (2) and HB (3) resemble each other with a side chain linked to a ring structure.…”
Section: Discussionsupporting
confidence: 84%
“…Structure-activity relationship (SAR) data for the three compounds and related molecules have been steadily emerging (Sakai et al 2002;Mizui et al 2004;Lagisetti et al 2008Lagisetti et al , 2013Lagisetti et al , 2014Albert et al 2009;Fan et al 2011;Gundluru et al 2011;Muller et al 2011;Villa et al 2012Villa et al , 2013Gao et al 2013;Ghosh and Chen 2013;Arai et al 2014;Effenberger et al 2014;Ghosh et al 2014a,b,c;He et al 2014). SSA (1), which is similar to FR901464 (Nakajima et al 1996b), meayamycin (Albert et al 2009), thailanstatins (Liu et al 2013), and sudemycins (Fan et al 2011), differs in structure relative to the other two compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromenes derivatives significant heterocycles that are known to have multiple biological activities 1 for instance, antibacterial, 2 antitumor, 3 sex pheromonal, 4 antimicrobial, 5 TNF-a inhibitory, 6 anticancer, 7 antifungal, 8 estrogenic, 9 antiviral 10 and anti-HIV. 11 Such compounds have also been applied in pigments, and insecticides 12 and therefore, a number of methods and catalysts have been reported for the synthesis of chromene derivatives such as, a [1-(n-butyl)-3-methylimidazolium hydroxide ( 31 Many of the above methods have their own advantages.…”
Section: Introductionmentioning
confidence: 99%